Delving into EFL Pre-Service Teachers’ Emotional Experiences: Professional Identity Construction in Online Teaching Practice Programs: - Khoiriyah; Widiati, Utami; Cahyono, Bambang Yudi; Rachmajanti, Sri (JEELS (Journal of English Education and Linguistics Studies), 2024)
This paper presents the online teaching practice program that influence EFL pre-service teachers’ (PSTs) emotional experiences as the pre-cursor of their professional identity construction. This study involved six   PSTs enrolled teaching practice program in an initial teacher education. Dialogic reflection before, during, and after teaching enactment was employed to dig up information about their emotional experiences in an online classroom setting. The data were analyzed using appraisal analysis (Martin and White, 2007) and thematic analysis. The results document negative emotional experiences such as feeling dissatisfaction, doubtful, and confusion which lead to positive emotional experiences, such as caring. Factors that influence PS Ts’ emotional experiences in online teaching practice are lack of Curriculum Knowledge (CrK), lack of subject-matter knowledge or Content Knowledge (CK), and lack of Pedagogical Knowledge (PK) in terms of assessing students’ competence, and the interlink between theory and practice. All PS Ts develop a good understanding of how to exploit technological tools by encouraging their self-concept. This study substantiates the importance of shared-space coaching for teacher mentors before they become an escort for PSTs who are going to be professional teacher mentors.